Local Wisdom as a Moral Ecology: Rethinking Character Education in Indonesia’s Cultural and Global Contexts - Afendi, Achmad Ruslan; Muhsinin, Umil; Wiratih, Hernawati W Retno (Journal La Edusci, 2025)
This study aims to examine how the values of local wisdom can be integrated in character education to form a generation with integrity, especially in the midst of the increasingly strong influence of globalization. This research also seeks to explore the relevance of local wisdom values in the context of education in Indonesia, and how it can support the formation of students' character. This study uses a qualitative approach with the type of literature study research (library research). Data was collected through a literature review of various relevant scientific journals, books, and articles. This study examines works that discuss character education, local wisdom, and the impact of globalization on education, as well as identify integration models that can be applied in the character education curriculum in Indonesia. The results of the study show that local wisdom values such as mutual cooperation, discipline, and honesty can be integrated in character education to strengthen student morale. This integration helps students understand and appreciate their culture, as well as build integrity. Key challenges include the influence of globalization and the lack of educators' understanding of local wisdom in the existing educational curriculum. This study introduces a new model to integrate local wisdom in character education, which can be applied in various schools in Indonesia. This research also contributes to the development of a character education curriculum based on local culture, as well as offers new insights to align education with traditional values that are relevant in the era of globalization.